WRKY transcription factors WRKY12 and WRKY13 interact with SPL10 to modulate age‐mediated flowering - Ma, Zhenbing; Li, Wei; Wang, Houping; Yu, Diqiu (Journal of integrative plant biology, 2020)
WRKY12 and WRKY13 are two WRKY transcription factors that play important roles in the control of flowering time under short‐day (SD) conditions. The temporally regulated expression of WRKY12 and WRKY13 indicates that they may be involved in the age‐mediated flowering pathway. However, their roles in this pathway are poorly understood. Here, we show that the transcription of WRKY12 and WRKY13 is directly regulated by SQUAMOSA PROMOTER BINDING–LIKE 10 (SPL10), a transcription factor downstream of the age pathway. Binding and activation analyses revealed that SPL10 functions as a positive regulator of WRKY12 and a negative regulator of WRKY13. Further mechanistic investigation revealed that WRKY12 and WRKY13 physically interact with SPL10 and that both of them bind to the promoter of miR172b. Thus, the WRKY12‐SPL10 and WRKY13‐SPL10 interactions facilitate and inhibit SPL10 transcriptional function, respectively, to regulate miR172b expression. Together, our results show that WRKY12 and WRKY13 participate in the control of age‐mediated flowering under SD conditions though physically interacting with SPLs and co‐regulating the target gene miR172b. In this study, we reported that WRKY12 and WRKY13 participate in the control of age‐mediated flowering under short‐day conditions through physically interacting with SPL10 and co‐regulating the target gene miR172b.